An Integrated Model of Social Capital and Open Innovation: Examining the Mediation Effect of Knowledge Acquisition and Knowledge Integration - Ganagambegai Laxamanan; Rabiah Eladwiah Abdul Rahim (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: Understanding the various effects that exist among social capital, knowledge acquisition, knowledge integration, and open innovation is the main purpose of this study. Design/methodology/approach: Data were gathered from 137 managers from Malaysian SMEs. Findings: The results of the analysis revealed that SC dimensions had insignificant impact on OI practices. The results also showed that, knowledge integration influence OI practices and mediate the relationship between SC dimensions and OI practices. This study also found that there is a significant positive relationship between SC dimensions and OI thru knowledge integration. The findings of this study thus provide many benefits for researchers and practitioners despite the presence of some limitations. Originality/value: This paper is original Paper type: Research article